INTEGRATING SPACE TECHNOLOGIES INTO UKRAINIAN ARCHITECTURAL DESIGN - Антоненко, І. В.; Агліуллін, Р. М.; Вишневська, О. В.; Кузьменко, В. В. (Art and Design, 2024)
Purpose: to investigate the process of implementation of space technologies in the field of Ukrainian architectural design, as well as to investigate the results of such implementation on both architectural design and technologies in construction. Methodology. Information-research and visual-analytical approaches are used in combination with methods of systematization and comparative analysis regarding the use of space technologies in architectural design. Results. The process of integrating space innovations into the field of architectural design is considered. It was determined that modularity, 3D printing and innovative materials used in space technologies are key factors that can be transformed into modern Ukrainian architectural design, and due to which it is possible to increase the reliability, energy efficiency and adaptation of design objects, in particular in cases of housing shortages (for refugees) or assistance to regions affected by natural (military) disasters. It is also demonstrated how the principles of vernacular architecture, traditionally based on local resources and methods, can be used in the future to shape modern buildings. Scientific novelty. The possibility of using space technologies in Ukrainian architectural design was studied, the peculiarities of their application in practice were revealed. The peculiarities and difficulties of their implementation in the design process have been revealed. Practical significance. The results of the research can be useful both for the development of design methods and techniques, and in other areas of research design for students, teachers and architects.